PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA DIGITAL TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 25 PADANG - Shafira, Vindi; Musdi, Edwin (Jurnal Edukasi dan Penelitian Matematika, 2024)
One measure of success in the learning process is the attainment of learning outcomes. However, grade VIII at SMP Negeri 25 Padang still struggle with maths. This is due to low student learning engagement. The Discovery Learning model combined with digital media was chosen as an effort to overcome this issue. This quasi-experimental research uses a nonequivalent posttest only control group design. The P-value of 0.002, below the significance level α = 0.05, was found after data analysis using the t-test. The Discovery Learning model using digital media is better in improving learning outcomes class VIII SMP Negeri 25 Padang compared to conventional learning.Keywords– Mathematics Learning Outcomes, Discovery Learning, Digital Media